Does love in the ivory tower fix the leaky pipeline? How academia’s homogamous relationships shape careers - Antonia Velicu; Manon Fauvelais; Julia Jerke; Heiko Rauhut; Bruno Lemaitre (PLoS ONE, 2026)
The persistent “leaky pipeline”, i.e., women remaining underrepresented in advanced academic roles, often links to the adverse impact of parenthood on women’s careers compared to men’s. This study delves into how the struggle to balance academic success and family life might be pushing female scientists out of academia, and how the less-studied concept of homogamy—here, the forming of heterosexual relationships between individuals with the same profession—influences academic careers. Drawing on data from the 2021 “Academic career, partnership, and family” survey by swissuniversities, this research pursues two objectives: assessing whether homogamous partnerships help mitigating career challenges faced by mothers, and investigating the broader impact of homogamy on academic careers and work-life balance. The findings show that homogamy is common among Swiss scientists. Homogamous women, especially when their partner works in the same institution, perceive parenthood as posing fewer career obstacles. Conversely, male scientists in such relationships state the opposite. Additionally, homogamous couples report benefiting from stimulating discussions and partner support while encountering greater mobility constraints. This research offers insights into how homogamy affects academic careers, providing a nuanced understanding of how academics navigate their pursuit of successful careers alongside personal lives.